2015
DOI: 10.1016/j.jenvrad.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical environmental transport of actinides and 137Cs from an arid radioactive waste disposal site

Abstract: Aeolian and pluvial processes represent important mechanisms for the movement of actinides and fission products at the Earth's surface. Soil samples taken in the early 1970's near a Department of Energy radioactive waste disposal site (the Subsurface Disposal Area, SDA, located in southeastern Idaho) provide a case study for studying the mechanisms and characteristics of environmental actinide and (137)Cs transport in an arid environment. Multi-component mixing models suggest actinide contamination within 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…A more likely reason for such a low calculated non‐nuclear weapons fallout ratio is that the direct fallout 137 Cs concentration correction is not an appropriate approach for this specific matrix, such as would be the case if the JSAC samples were collected from a disturbed or low nuclear weapons fallout deposition location. One independent technique for evaluating whether such is the case is comparison of Cs/Pu ratios; as Cs and Pu from global nuclear weapons fallout have been shown to be strongly correlated in Japan and other locations, decreases in global fallout 137 Cs concentrations due to soil disturbances typically result in comparable decreases in 239+ 240 Pu concentrations . The JSAC soil has been certified to contain 0.025 ± 0.001 Bq of 239+ 240 Pu per kg soil with an isotope ratio consistent with global nuclear weapons fallout (0.180 ± 0.009) .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A more likely reason for such a low calculated non‐nuclear weapons fallout ratio is that the direct fallout 137 Cs concentration correction is not an appropriate approach for this specific matrix, such as would be the case if the JSAC samples were collected from a disturbed or low nuclear weapons fallout deposition location. One independent technique for evaluating whether such is the case is comparison of Cs/Pu ratios; as Cs and Pu from global nuclear weapons fallout have been shown to be strongly correlated in Japan and other locations, decreases in global fallout 137 Cs concentrations due to soil disturbances typically result in comparable decreases in 239+ 240 Pu concentrations . The JSAC soil has been certified to contain 0.025 ± 0.001 Bq of 239+ 240 Pu per kg soil with an isotope ratio consistent with global nuclear weapons fallout (0.180 ± 0.009) .…”
Section: Resultssupporting
confidence: 90%
“…One independent technique for evaluating whether such is the case is comparison of Cs/Pu ratios; as Cs and Pu from global nuclear weapons fallout have been shown to be strongly correlated in Japan [37] and other locations, [39,41] decreases in global fallout 137 Cs concentrations due to soil disturbances typically result in comparable decreases in 239 +240 Pu concentrations. [37,39,42] The JSAC soil has been certified to contain 0.025 ± 0.001 Bq of 239+240 Pu per kg soil with an isotope ratio consistent with global nuclear weapons fallout (0.180 ± 0.009). [33,34] When this concentration of global fallout Pu is combined with the 137 Cs/ 239+240 Pu activity ratio from global fallout observed in northern Japan (22.4 ± 4.2), [35] a 137 Cs concentration from global nuclear weapons fallout of the order of 6•10 -4 Bq/g is calculated, representing 0.5% of the total 137 Cs in the JSAC soil sample.…”
Section: Evaluating Mixing With Global Nuclear Weapons Falloutmentioning
confidence: 99%
“…27 As two pluvial flooding events occurred at the SDA during the 1960′s, it has been suggested that particles containing 137 Cs from global + regional fallout could have been selectively deposited in the drainage ditch via surface water sedimentation processes in a manner similar to that observed by Snyder et al for 137 Cs at Lake Mead (albeit on a much smaller scale). 12 A third possible source of 137 Cs contamination is from 137 Cs waste within the SDA; although the inventory of the SDA is not completely known due to inadequate record keeping, > 10 5 Ci of 137 Cs resulting from dozens of different waste generators representing over 230 different processes has been docu- mented.…”
Section: Environmental Science and Technologymentioning
confidence: 81%
“…This study demonstrates the current capabilities and limitations of environmental contamination source term attribution using Cs data alone. Samples taken in the early 1970′s near the Subsurface Disposal Area (SDA) at Idaho National Laboratory (INL) represent a complicated case study, as three distinct emission sources (representing dozens of different waste generators and over 230 unique processes) have been suggested as the source of the 137 Cs around this site. , Specifically, this study demonstrates how 137 Cs surface soil distribution patterns, 135 Cs/ 137 Cs ratios, known Cs chemistry at this site, and historical documents can be utilized together to identify the original source of the 137 Cs contamination, the primary release event, and the mechanism(s) of environmental transport. Identification of these attributes in this work enables refining the total number of possible waste generators down from dozens to a single generator.…”
Section: Introductionmentioning
confidence: 99%
“…Transport of Radioactive Waste. Snow et al, (2015) provided a case study for studying the mechanisms and characteristics of environmental actinide and 137 Cs transport in an arid environment. This study data suggest flooding resulted in mechanical transport of contaminated particles into the area between the the subsurface disposal area and a flood containment dike in the northeastern corner, following which subsequent contamination spreading in the northeastern direction resulted from wind transport of discrete particles.…”
mentioning
confidence: 99%